Axiological Foundations of Business Ethics in the Post-Socialist Russia: Intercultural Context - Dzialoshinskiy, Iosif; Pilgun, Maria (International Journal of Economics and Financial Issues, 2015)
The article describes the analysis of value basis of business ethics in various countries. The analysis is based on the questionnaire survey of respondents from Russia, as well as Spain, Italy, France, Germany, England and the USA. According to the aim of the study - to investigate the share and the linkages between reported values of entrepreneurs with informal practices as well as with public expectations, empirical data collection took place in May – December 2013. Self-administrated questionnaire (also web-based) was used in the study. The data for the survey was collected using UNIPARK platform. It was demonstrated that many traditional theories developed in this area need to be revised. A sharp contradiction between actual values of entrepreneurs and public expectations stated in sets of codes and concepts of social responsibility was revealed. It was concluded that the informal corrupt practices exist due to the difficulty of entrepreneurs to comply with public attitudes without restructuring their own value system. Keywords: business ethics, ethical regulation, values JEL Classifications: D12; D22; D23; R12